(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Molecular-physics related to the significant progress achieved at the atomic-molecular level, as well as the wide use of new physics, deeper penetration into the essence of micro-processes in the building processes and the consideration of corpuscular models depending on the atomic-molecular structure, molecules that form wet materials, atoms, it is recommended to take into account the interaction forces between ions and bodies. Such an approach to the study of drying processes is said to give positive results in the analysis of the processes developing inside the material. It has been written about the interaction of moisture with the dry skeleton of the body, the effect of surfactants on the wet material, and also led to the introduction of special methods of delivery of various energies to the drying areas